2015
DOI: 10.1002/2015je004816
|View full text |Cite
|
Sign up to set email alerts
|

The Martian atmospheric ion escape rate dependence on solar wind and solar EUV conditions: 1. Seven years of Mars Express observations

Abstract: More than 7 years of ion flux measurements in the energy range 10 eV-15 keV have allowed the ASPERA-3/IMA (Analyzer of Space Plasmas and Energetic Ions/Ion Mass Analyzer) instrument on Mars Express to collect a large database of ion measurements in the Mars environment, over a wide range of upstream solar wind (density and velocity) and radiation (solar EUV intensity) conditions. We investigate the influence of these parameters on the Martian atmospheric ion escape rate by integrating IMA heavy ion flux measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
136
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 34 publications
19
136
1
Order By: Relevance
“…One possible explanation is that we did not include the neutral wind in our simulations, which can greatly affect the ion loss [Brecht and Ledvina, 2014b]. On the other hand, the recent paper published by Ramstad et al [2015] showed that the solar wind density and velocity can greatly affect the ratio of escape rate between low and high solar EUV conditions. They adopted more than 7 years of ion flux measurements in the energy range 10 eV to 15 keV from ASPERA-3/IMA instrument on board MEX.…”
Section: Effects Of Solar Cycle Conditionsmentioning
confidence: 98%
“…One possible explanation is that we did not include the neutral wind in our simulations, which can greatly affect the ion loss [Brecht and Ledvina, 2014b]. On the other hand, the recent paper published by Ramstad et al [2015] showed that the solar wind density and velocity can greatly affect the ratio of escape rate between low and high solar EUV conditions. They adopted more than 7 years of ion flux measurements in the energy range 10 eV to 15 keV from ASPERA-3/IMA instrument on board MEX.…”
Section: Effects Of Solar Cycle Conditionsmentioning
confidence: 98%
“…Its contribution is significant in the 10 24 −10 25 s −1 range for Mars and Venus (Lammer 2013;Ramstad et al 2015;Masunaga et al 2013), but decreases rapidly when the magnetosphere grows with increasing magnetic moment (Appendix A.2 and Fig. 3).…”
Section: Escape Processesmentioning
confidence: 99%
“…The authors also derived an empirical expression for the Martian escape rate versus solar activity F10.7 index and the sunspot number, which is a useful tool to derive the accumulated ion escape rate from Mars based on historical records of solar activity, with big potentials to back to the young Sun epoch. More recently, Ramstad et al (2015) have further quantified the ion escape rate with respect to upstream solar wind density, velocity, and EUV conditions. The most interesting trend is the decrease Dubinin et al (2011) of the atmospheric erosion with increasing solar wind density, in particular during low solar EUV intensity conditions.…”
Section: Atmospheric Escape: Physical Processes and Exospheric Observmentioning
confidence: 99%